2020
DOI: 10.1093/jas/skaa178
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal bacterial community composition and concentrations of estradiol at the time of artificial insemination in Brangus heifers

Abstract: The knowledge surrounding the bovine vaginal microbiota and its implications on fertility and reproductive traits remains incomplete. The objective of the current study was to characterize the bovine vaginal bacterial community and estradiol concentrations at the time of artificial insemination (AI). Brangus heifers (n = 78) underwent a 7-d Co-Synch + controlled internal drug release estrus synchronization protocol. At AI, a double-guarded uterine culture swab was used to sample the anterior vaginal tract. Imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 36 publications
2
15
0
4
Order By: Relevance
“…Results from another study indicated that unclassified Enterobacteriaceae (21.05%), Ureaplasma (4.37%), and unclassified Bacteroidaceae (2.49%) were the most predominant [17]. At the phyla level, Tenericutes (36%), Proteobacteria (30%), Fusobacteria (7.6%), and Firmicutes (1.8%) were the most abundant [47]. In the study by Deng et al (2019), Firmicutes (31.57%), Proteobacteria (24.08%), Bacteroidetes (12.96%), and Tenericutes (4.95%) were the most prevalent in the vagina.…”
Section: Vaginamentioning
confidence: 99%
See 2 more Smart Citations
“…Results from another study indicated that unclassified Enterobacteriaceae (21.05%), Ureaplasma (4.37%), and unclassified Bacteroidaceae (2.49%) were the most predominant [17]. At the phyla level, Tenericutes (36%), Proteobacteria (30%), Fusobacteria (7.6%), and Firmicutes (1.8%) were the most abundant [47]. In the study by Deng et al (2019), Firmicutes (31.57%), Proteobacteria (24.08%), Bacteroidetes (12.96%), and Tenericutes (4.95%) were the most prevalent in the vagina.…”
Section: Vaginamentioning
confidence: 99%
“…A comparison of the results from these two recent studies reveals that the proportions of the predominant microbial populations differ significantly between individuals. Phylum: Tenericutes (36%), Proteobacteria (30%), Fusobacteria (7.6%), and Firmicutes (1.8%) [47].…”
Section: Vaginamentioning
confidence: 99%
See 1 more Smart Citation
“…Some of these factors, especially pH, can directly affect important aspects of reproduction such as sperm motility, fertilization rate, and early embryonic development and survival (Wang et al, 2020;Ravel et al, 2021). Only a handful of studies have offered insights into the vaginal microbial communities within ruminants (Swartz et al, 2014;Laguardia-Nascimento et al, 2015;Deng et al, 2019;Messman et al, 2020) and associated those findings with different reproductive outcomes (Swartz et al, 2014;Deng et al, 2019;Messman et al, 2020). Compared with other ruminants, knowledge about the microbial communities in the reproductive tract of sheep is even less.…”
Section: Introductionmentioning
confidence: 99%
“… Nugeyre et al (2019) reported that progesterone can affect the abundance of some microorganisms in the vagina of female cynomolgus macaques. Messman ( Messman et al, 2020 ) reported that estradiol had a certain effect on the bacterial composition of Brangus heifers vagina. However, the corresponding relationship between hormones and vaginal microbiome in giant pandas still needs to be revealed by further study.…”
Section: Discussionmentioning
confidence: 99%